VCO‐based ADC with a simplified DAC for non‐linearity correction. Issue 13 (1st June 2018) - Quintero, A.; Perez, C.; Gutierrez, E.; Hernandez, L.
Abstract : The performance of open‐loop ADCs implemented with VCOs is limited by VCO non‐linearity and first‐order noise shaping. The resolution limitation imposed by first‐order noise shaping can be compensated by a ring oscillator VCO with many output phases. Linearity can also be improved by using a feedback loop around the VCO closed with a DAC. However, a long ring oscillator may require a DAC with a prohibitive number of bits if feedback is used to compensate distortion. This Letter proposes an ADC architecture based on the Leslie‐Singh Sigma‐Delta ( Σ Δ ) modulator that allows to implement a distortion correction loop around a VCO with a simplified DAC of few levels, yet keeping a large number of output quantisation levels to maintain resolution. The Letter discusses the system‐level architecture and shows an implementation circuit example to verify the effective correction of distortion.